Switzerland : 2012 Article IV Consultation: Staff Report; Public Information Notice on the Executive Board Discussion; Statement by the Executive Director for Switzerland. (IMF Staff Country Reports; Country Report ;, 2012)
This Article IV Consultation reports that Switzerland's exchange rate floor, seen as credible by the markets, has halted appreciation and helped shore up the economy. Once growth recovers and inflation reaches more comfortable levels, maintaining the exchange rate commitment risks stoking inflation and hence, a return to free floating would be desirable. The risk of a real estate bubble has been heightened by loose monetary conditions, and new macroprudential instruments are under consideration to address this risk.